"Deep-seated Abnormality": Military Psychiatry, Segregation, and Discourses of Black "Unfitness" in World War II. (June 2019) - Aragon, Margarita
This article examines the construction of "unfit" black masculinity in institutional and medical discourses of the American military during World War II. Examining the military medical literature on "maladjustment" in context of the armed forces practice of segregation, I argue that by ignoring the impact of segregation, military psychiatrists reproduced linkages between blackness and "defect." Despite the absence of direct assertions of racial hierarchy, these discourses thus implicitly, and sometimes explicitly, construed black manhood as alternately feeble and menacing, but above all as "abnormal" in both mind and body. Examining articles from psychiatric and military medical journals, as well as the internal documents of military officials, I investigate these claims in regard to the conceptualization and management of "constitutional defects" and psychosomatic illness.